Telemedicine and Remote Monitoring as an Adjunct to Medical Management of Bronchiectasis - Soontharee Congrete (MDPI AG, 2021)
The limited resources and the practice of social distancing during the COVID pandemic create a paradigm shift in the utilization of telemedicine in healthcare. However, the implementation of best practices is hampered in part by a lack of literature devoted to telehealth in bronchiectasis. In this commentary, we examine multiple approaches to structuring of telemedicine care for patients with bronchiectasis, highlight current evidence-based interventions that can be incorporated into the management of bronchiectasis, and describe our experience with telemedicine at the University of Connecticut Center for Bronchiectasis Care during the COVID-19 pandemic. The structural model must be adapted to different local dynamics and available technologies with careful attention to patient characteristics and access to technology to avoid the potential paradoxical effects of increasing patients’ burden and healthcare disparities in underserved populations.